A preliminary study on the impact of UCK2 knockdown in DLD-1 colorectal cells treated with DHODH inhibitor - Mohamad Fairus Abdul Kadir,; Puteri Shafinaz Abdul-Rahman,; Nellore, Kavitha; Shatrah Othman, (Penerbit Universiti Kebangsaan Malaysia, 2021)
Brequinar sodium (BQR) is a well-studied inhibitor of the dihydroorotate dehydrogenase (DHODH) enzyme. Both the DHODH and uridine-cytidine kinase 2 (UCK2) enzymes have been reported to be over-expressed in cancer cells to maintain the cells high demand for DNA and RNA for their proliferation. In this study, we aim to further sensitize cells to the effects of BQR by knocking down the UCK2 activity. In DLD-1 UCK2 knockdown cells, no change in the sensitivity of cells to BQR was observed. Uridine is known to reverse the anti-proliferative effect of DHODH inhibitors via the salvage pathway. We observed abrogation of approximately 30% of the uridine reversal effect in UCK2 knockdown cells compared to the wild type cells. Our finding indicates that the loss of UCK2 activity in the salvage pathway did not enhance the BQR-mediated cell proliferation inhibition but it abrogates the uridine reversal in the cells.